Interactions of wheat cultivars and supplemental enzyme in diet of broiler chickens on growth performance, carcass characteristics, intestinal morphometric features, and blood parameters - Seyedkamyar Seyedoshohadaei; Mehran Torki; Akbar Yaghoubfar; Alireza Abdolmohammadi (Journal of Agriculture and Food Research)
This study investigated the effects of wheat cultivar and enzyme supplementation on growth, carcass traits, intestinal morphology, and blood parameters in broiler chickens. A total of 648 male chicks were assigned to 9 diets: four Iranian wheat cultivars (Sardari, Azar2, Pishgam, Sirvan) with and without enzyme supplementation, plus a corn-based control (6 replicates/diet, 12 birds/pen). Diets were iso-caloric and iso-nitrogenous. Chicks were fed for 39 days. Corn-based diets generally led to higher feed intake (FI) throughout the study compared to most wheat-based diets. However, during the finishing period (25–39 days), broilers fed diets containing Sardari and Azar2 wheat achieved the best weight gain and feed conversion ratio (FCR) compared to those fed Sirvan cultivar. Most of the carcass traits were not affected by the experimental treatments. Blood glucose, aspartate aminotransferase (AST) activity, and high-density cholesterol (HDL) levels were all noticeably affected by the type of wheat in the diet. Jejunum length and cecum weight were greatest in birds fed different wheat cultivars, while the corn-based diet resulted in the shortest jejunum and cecum length. Adding enzymes to the Pishgam cultivar diet increased the length of the ileum. significant interactions between wheat cultivar and enzyme were observed for jejunal villi characteristics (length, thickness, number) and muscle layer thickness, Broilers fed the Sardari diet exhibited the deepest crypts and lowest villi length-to-crypt depth ratio. The study concluded that there is a significant effect of wheat cultivar diversity on broiler performance traits, blood chemistry, carcass characteristics, and gut health. The findings also suggest that the selected enzyme may not be effective in all wheat cultivars due to the absence of a consistent wheat cultivar-enzyme interaction.